2013
DOI: 10.4321/s1134-80462013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico y tratamiento del dolor irruptivo oncológico: recomendaciones de consenso

Abstract: Introduction objectives: Breakthrough cancer pain (BTcP) is an acute exacerbation of baseline pain. The clinicians involved in its management have different diagnostic and therapeutic criteria.In order to facilitate decision making in usual clinical practice, 8 reference experts from 4 scientific associations involved in the management of patients with cancer pain have developed this Consensus Document.Methods: After an initial search on the most relevant publications in BTcP literature, a set of preliminary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
1
18
0
4
Order By: Relevance
“…Breakthrough cancer pain was fi rst defi ned by Portenoy et al in 1990 [7], as 'a transitory exacerbation of pain experienced by patients undergoing long-term opioid treatment for cancerrelated pain whose baseline pain is adequately controlled', but there has been controversy with respect to this defi nition over the past two decades. Some international guidelines recommend the defi nition of BTcP derived from the original by Portenoy [9][10][11][12], whereas others have established their own defi nition [13][14][15]. The main discrepancy is the fact that BTcP can also occur in the absence of background cancer pain and regardless of opioid treatment [16,17].…”
Section: Considerations On the Defi Nition Of Btcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Breakthrough cancer pain was fi rst defi ned by Portenoy et al in 1990 [7], as 'a transitory exacerbation of pain experienced by patients undergoing long-term opioid treatment for cancerrelated pain whose baseline pain is adequately controlled', but there has been controversy with respect to this defi nition over the past two decades. Some international guidelines recommend the defi nition of BTcP derived from the original by Portenoy [9][10][11][12], whereas others have established their own defi nition [13][14][15]. The main discrepancy is the fact that BTcP can also occur in the absence of background cancer pain and regardless of opioid treatment [16,17].…”
Section: Considerations On the Defi Nition Of Btcpmentioning
confidence: 99%
“…In 2012, an association of Spanish medical doctors, composed of palliative care, pain specialists, oncologists and radiation oncology experts, produced a consensus document with a series of guidelines to properly diagnose and treat BTcP patients. BTcP at that time was defi ned as 'a transient, highly intense exacerbation of pain of short duration (less than 20-30 minutes) appearing through a stable pain baseline that can be controlled by opioid treatment' [13]. Although this defi nition is still valid, some clarifi cations are needed.…”
Section: Considerations On the Defi Nition Of Btcpmentioning
confidence: 99%
“…Testing the usability of these tools revealed that definitions of Davies [6] and Escobar et al [17] along with the Davies algorithm were the most used. One of the difficulties attributed to assess the prevalence of BTcP in the cancer population lies in the variety of definitions that exist and are used for BTcP.…”
Section: Principal Findingsmentioning
confidence: 99%
“…After testing the different level of usage of this diagnostic workflow, BTcP definition by Davies et al [6] and Escobar et al [17] along with the Davies algorithm were shown to be mostly used (Fig. 3).…”
Section: Mobile Application Intervention In Patientsmentioning
confidence: 99%
See 1 more Smart Citation